Isolation and identification of a phenolic antioxidant from Aloe barbadensis - Lee, K.Y.; Weintraub, S.T.; Yu, B.P.
A potent antioxidative compound has been isolated from a methanolic extract of Aloe barbadensis Miller using a combination of column and thin-layer chromatography. The antioxidant activity of this substance was similar to that of a-tocopherol as assessed in vitro using rat brain homogenates. On the basis of electrospray ionization and electron-impact ionization mass spectra in combination with reversed-phase, high-performance liquid chromatographic behavior, this compound has been identified as 8-C-b-D-[2-O-(E)-coumaroyl]glucopyranosyl-2-[2-hydroxy]- propyl-7-methoxy-5-methylchromone.
Keywords: ALOE BARBADENSIS; PLANT PHENOLS; ANTIOXIDANT; FREE RADICALS